Experience of using the natural terpens complex for prevention and treatment of respiratory tract diseases at preschool age - A. M. Zakirova; T. G. Fetisova; L. F. Rashitov; E. L. Rashitova (Лечащий Врач)
The authors shared experience of using a complex of natural terpenes to prevent respiratory tract diseases in preschool children in organized groups. A total of 7129 children aged 3–7 years were examined, which included: a pediatrician examination, anamnestic data analysis, an observation sheet filling, a polymerase chain reaction for the presence of Epstein–Barr virus in nasopharyngeal swabs before and after the examination.